Modellierung der Mechanik und der effektiven Transporteigenschaften von partikulären Kathoden sowie deren Einfluss auf die elektrochemische Performance von Lithium-Ionen-Batterien - Becker, Verena Irene (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
In the present work, lithium-ion battery cathodes and battery half-cells are numerically investigated. Of main interest is the influence of the calendering of an electrode during its manufacture on the mechanically induced changes in the microstructure and the resulting performance characteristics of a cell. In particular, the influence of varying particle shape and plastic material properties is considered.